2020
DOI: 10.1007/s10834-020-09733-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housework on Wages: A Study of Migrants and Native-Born Individuals in Germany

Abstract: To increase labour market participation among migrants, an increase in female labour market participation is important, with wages being a significant incentive. In research on the gender wage gap, the consideration of housework has been a milestone. Gender differences in housework time have always been much greater among migrants than among native-born individuals. Based on data obtained from the German Socio-Economic Panel from 1995 to 2017, this study questioned whether housework affects the wages of migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…Second, these routine housework tasks are more relevant for the total housework, as this accounts for a large amount of total work (75 percent). Third, previous research revealed that particularly routine housework negatively affects wages (e.g., Noonan, 2001), especially for female migrants (Fendel, 2020).…”
Section: Outcome Variablesmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, these routine housework tasks are more relevant for the total housework, as this accounts for a large amount of total work (75 percent). Third, previous research revealed that particularly routine housework negatively affects wages (e.g., Noonan, 2001), especially for female migrants (Fendel, 2020).…”
Section: Outcome Variablesmentioning
confidence: 96%
“…In addition, when more time is made available, there is more space for productive activities outside of the household: women have more time to participate in the labor market and be active citizens (Bianchi et al, 2000). The importance of these arguments is further strengthened in the case of immigrant women, many of whom face additional hurdles in host societies, such as fewer employment opportunities and, if employed, lower wages, more precarious working conditions, lack of language skills, challenges in recognition of their educational credentials, and housing issues (Fendel, 2020;Frank & Hou, 2015;Gowayed, 2019;Koyama, 2015). These difficulties have the capacity to reinforce the traditional division of labor in immigrant families and are even more pronounced for refugees who also need to safeguard family well-being after potentially traumatic experiences (for review, see Kogan & Kalter, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…indépendantes et primo-arrivantes (arrivées célibataires ou sans conjoint) (Cristina Samper et Kreyenfeld, 2021[44] ; Ortensi, 2015[45]). En Espagne, le taux de fécondité des immigrées d'Amérique latine est inférieur à celui observé dans leurs pays d'origine, constat qui tient en partie à la sélectivité migratoire et au fait que ces femmes ne sont pas toujours accompagnées de leurs enfants.…”
unclassified
“…Cela est particulièrement vrai lorsque les inégalités de revenus sont importantes ou lorsque les politiques sociales et familiales sont moins développées. Les estimations réalisées par Farré, González et Ortega (2011[45]) en Italie, par exemple, montrent que l'immigration peut expliquer un tiers de l'augmentation du taux d'emploi des femmes diplômées de l'enseignement supérieur en assurant la garde des enfants et des personnes âgées (avant 2008). Aux États-Unis, Furtado et Hock (2010[46]) concluent qu'une baisse du coût des services d'aide à la personne, assurés par une population immigrée peu instruite, permet aux femmes très instruites nées dans le pays de concilier maternité et travail rémunéré.Le travail à temps partiel concerne aussi bien les mères nées dans le pays que celles nées à l'étranger mais, pour les femmes immigrées, il s'agit plus souvent d'emplois précaires à temps partiel subiDans de nombreux pays de l'OCDE, les mères sont moins susceptibles d'effectuer de longues heures de travail et elles ont souvent recours à l'emploi à temps partiel pour combiner travail et responsabilités familiales.…”
unclassified